Congenital meningocoele presenting in an adult - Ramdasi, Raghvendra V. (Medknow Publications & Media Pvt Ltd, 2014)
A 53-year-old male patient presented with low back pain radiating to both lower limbs for 2 years and urinary incontinence for 2 months. He had swelled over his lower back since birth. The neurological examination revealed a decreased perianal sensation. Local examination of the lumbar swelling showed a brilliantly transilluminant, cystic midline swelling in the lumbar area with underlying spina bifida. Magnetic resonance imaging revealed a low-lying conus at L3 level associated with spina bifida at L5 and a meningocoele sac. The patient underwent excision of the meningocoele and detethering of cord by extirpation of hypertrophied filum terminale. The patient had an immediate relief of his symptoms. At 3 month follow-up the lumbar wound had healed well, and there was a significant improvement in the perianal hypoesthesia. The adult presentation of a congenital meningocoele and spinal dysraphism is rare, especially in the fifth decade. The possible causes of this delayed presentation are analyzed, and the relevant literature on the subject is presented.